The Impact of Implementation Virtual Reality (VR) on Pain Levels Among Children with Invasive Procedures: A Literature Review - Perdani, Agni Laili; Mutiar, Astri; Nazmudin, Yusup (KnE Life Sciences, 2021)
The volume of hospitalized pre-school children has increased in recent years. More than 30% children have experienced hospital treatment and 5% have been treated several times in the hospital. They will undergo painful procedures with physical and psychological impacts. Various technological approaches to pain management have been developed, including the use of virtual reality therapy to reduce pain in pediatric patients. The purpose of this study is to conduct a literature review to the impact of using Virtual Reality (VR) on pain level among children undergoing invasive procedures. Literature review was conducted from 2010-2020 at the five largest databases consist of Pubmed, Google Scholar, CINAHL, Medline and Psycinfo by using keywords “Virtual Reality” “Pain”, “Children Pain”, “Pediatric Pain”, “Virtual Reality and Children Pain” and “Virtual Reality and ‘Pediatric Pain. From four articles discussed both acute and chronic pain, VR can be used to reduce pain or other symptoms related physiological stress during hospitalization Keywords: Children, Pediatric, Pain, Hospitalization and Virtual Reality